Encephalitis related to immunotherapy for lung cancer: Analysis of a multicenter cohort. (May 2020) - Sanchis-Borja, Mateo; Ricordel, Charles; Chiappa, Anne Marie; Hureaux, José; Odier, Luc; Jeannin, Gaelle; Descourt, Renaud; Gervais, Radj; Monnet, Isabelle; Auliac, Jean-Bernard; Chouaïd, Christos
Highlights: Immune related encephalitis is a rare but serious complication of anti–PD-1/PD-L1 immunotherapy. Characteristics from NSCLC patients presenting immune related encephalitis, were evaluated retrospectively. Prognosis is good when management, particularly corticosteroids, are started early. Abstract: Introduction: Using immune-checkpoint inhibitors (ICIs) to manage cancer is associated with various immune-related adverse events. Central and/or peripheral neurological disorders are rare and potentially serious. We analyzed the characteristics of non-small–cell lung cancer (NSCLC) patients who developed immune-related encephalitis under anti–programmed-death protein-1 or its ligand (PD-1/PD-L1). Methods: Clinical, biological and radiological characteristics of ICI-treated NSCLC patients with immune-related encephalitis, from 6 centers, were evaluated retrospectively. Results: The 6 centers included 9 patients: all men, all smokers, median (range) age 67 (48–77) years, 78% adenocarcinomas, first- or second-line ICI for 5 and 4 patients, respectively. Two patients had non-active cerebral metastases at ICI onset. A median of 5 (1–22) ICI infusions preceded neurological symptoms, the most frequent being confusion (78%), fever (45%) and cerebellar ataxia (33%). CSF analyses revealed a median white blood cell count of 22/mm 3 (1–210/mm 3 ), with hyperlymphocytosis in 8 patients and high protein levels in all. All bacteriological and virological analyses were negative. Cerebral MRI was considered normal for 5 patients; 4 patients had FLAIR hypersignals consistent with brain parenchyma inflammation. Three patients required intensive care. All patients received corticosteroids (different doses), a median of 8.5 (6–18) days post-onset. Corticosteroids achieved rapid symptom regression without sequelae in 8 patients. The last patient, with the longest time until corticosteroid introduction, died. ICIs were never restarted in any patient. Conclusion: Immune encephalitis, a rare but serious complication of anti–PD-1/PD-L1 therapy, carries a good prognosis when managed with early corticosteroids.